Atendimento educacional a alunos com talento matemático e sua influência no desempenho escolar - Simplício, Micheline Idalga de Brito (2013)
There are many challenges that the educational system needs to face to offer an education of quality searching the proper attendance to the cognitive demands of all the students. This research had, as a main aim, to analyze the New Talent Project of UFS. Identifying its influence in the school performance of the participants in the school performance of the participants we used a methodology with a qualitative approach having as procedure the case study of ethnography base because it involves a group for an intensive analysis of a specific situation; before this we tried to collaborate with the nowadays discussion about the educational attendance with students with gift and talent in the field of mathematics. The instruments used in the collect of data were open and semi-structured, questionary, scale of self-evaluation of academic performance, document and record to a positive influence of the participation in the new talent project in the school performance of the students, in spite of other variables interfered in this process. So there results suggest the meaningful importance of this environmental catalyzer (new talent project) for the student with mathematical talent in his development in the scientific and mathematical fields